New approach for estimating risk of miscarriage after chorionic villus sampling. (17th October 2020) - Gil, M. M.; Molina, F. S.; Rodríguez‐Fernández, M.; Delgado, J. L.; Carrillo, M. P.; Jani, J.; Plasencia, W.; Stratieva, V.; Maíz, N.; Carretero, P.; Lismonde, A.; Chaveeva, P.; et al.
ABSTRACT: Objective: To estimate the risk of miscarriage associated with chorionic villus sampling (CVS). Methods: This was a retrospective cohort study of women attending for routine ultrasound examination at 11 + 0 to 13 + 6 weeks' gestation at one of eight fetal‐medicine units in Spain, Belgium and Bulgaria, between July 2007 and June 2018. Two populations were included: (1) all singleton pregnancies undergoing first‐trimester assessment at Hospital Clínico Universitario Virgen de la Arrixaca in Murcia, Spain, that did not have CVS (non‐CVS group); and (2) all singleton pregnancies that underwent CVS following first‐trimester assessment at one of the eight participating centers (CVS group). We excluded pregnancies diagnosed with genetic anomalies or major fetal defects before or after birth, those that resulted in termination and those that underwent amniocentesis later in pregnancy. We used propensity score (PS) matching analysis to estimate the association between CVS and miscarriage. We compared the risk of miscarriage of the CVS and non‐CVS groups after PS matching (1:1 ratio). This procedure creates two comparable groups balancing the maternal and pregnancy characteristics that are associated with CVS, in a similar way to that in which randomization operates in a randomized clinical trial. Results: The study population consisted of 22 250 pregnancies in the non‐CVS group and 3613 in the CVS group. The incidence of miscarriage in the CVS group (2.1%; 77/3613) was significantly higher than that in the non‐CVS group (0.9% (207/22 250); P  < 0.0001). The PS algorithm matched 2122 CVS with 2122 non‐CVS cases, of which 40 (1.9%) and 55 (2.6%) pregnancies in the CVS and non‐CVS groups, respectively, resulted in a miscarriage (odds ratio (OR), 0.72 (95% CI, 0.48–1.10); P  = 0.146). We found a significant interaction between the risk of miscarriage following CVS and the risk of aneuploidy, suggesting that the effect of CVS on the risk of miscarriage differs depending on background characteristics. Specifically, when the risk of aneuploidy is low, the risk of miscarriage after CVS increases (OR, 2.87 (95% CI, 1.13–7.30)) and when the aneuploidy risk is high, the risk of miscarriage after CVS is paradoxically reduced (OR, 0.47 (95% CI, 0.28–0.76)), presumably owing to prenatal diagnosis and termination of pregnancies with major aneuploidies that would otherwise have resulted in spontaneous miscarriage. For example, in a patient in whom the risk of aneuploidy is 1 in 1000 (0.1%), the risk of miscarriage after CVS will increase to 0.3% (0.2 percentage points higher). Conclusions: The risk of miscarriage in women undergoing CVS is about 1% higher than that in women who do not have CVS, although this excess risk is not solely attributed to the invasive procedure but, to some extent, to the demographic and pregnancy characteristics of the patients. After accounting for these risk factors and confining the analysis to low‐risk pregnancies, CVS seems to increase the risk of miscarriage by about three times above the patient's background risk. Although this is a substantial increase in relative terms, in pregnancies without risk factors for miscarriage, the risk of miscarriage after CVS remains low and similar to, or slightly higher than, that in the general population. © 2020 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Nuevo enfoque para estimar el riesgo de aborto después de una biopsia de vellosidades coriónicas Objetivo: Estimar el riesgo de aborto asociado con la biopsia de vellosidades coriónicas (BVC). Métodos: Se trata de un estudio retrospectivo de cohorte de mujeres que acudieron a un examen ecográfico de rutina entre las 11+0 y las 13+6 semanas de gestación a una de entre un total de ocho centros de medicina fetal en España, Bélgica y Bulgaria, entre julio de 2007 y junio de 2018. En el estudio se incluyeron dos poblaciones: 1) todos los embarazos con feto único sometidos a evaluación del primer trimestre en el Hospital Clínico Universitario Virgen de la Arrixaca de Murcia (España), a las que no se les hizo una BVC (grupo no BVC); y 2) todos los embarazos con feto único sometidos a BVC tras la evaluación del primer trimestre en uno de los ocho centros participantes (grupo BVC). Se excluyeron los embarazos diagnosticados con anomalías genéticas o defectos fetales importantes antes o después del nacimiento, los que resultaron en una interrupción y los que más tarde se sometieron a amniocentesis durante el embarazo. Para estimar la relación entre la BVC y el aborto espontáneo se utilizó el pareamiento por puntaje de propensión (PPP). Se comparó el riesgo de aborto de los grupos BVC y no BVC después del pareamiento PPP (razón 1:1). Este procedimiento creó dos grupos comparables en los que las características de la madre y el embarazo que se asocian con la BVC estaban equilibradas, de manera similar a cómo funciona la aleatorización en un ensayo clínico aleatorizado. Resultados: La población de estudio consistió en 22.250 embarazos en el grupo no BVC y 3.613 en el grupo BVC. La incidencia de abortos en el grupo BVC (2, 1%; 77/3.613) fue significativamente mayor que en el grupo no BVC (0, 9% (207/22.250); P<0, 0001). El algoritmo del PPP emparejó 2.122 BVC con 2.122 casos no BVC, de los cuales 40 (1, 9%) y 55 (2, 6%) embarazos en los grupos BVC y no BVC, respectivamente, resultaron en un aborto espontáneo (razón de momios (RM), 0, 72 (IC 95%, 0, 48–1, 10); P=0, 146). Se encontró una interacción significativa entre el riesgo de aborto espontáneo después de una BVC y el riesgo de aneuploidía, lo que sugiere que el efecto de la BVC en el riesgo de aborto espontáneo difiere según las características del contexto. Concretamente, cuando el riesgo de aneuploidía es bajo, el riesgo de aborto después de una BVC aumenta (RM, 2, 87 (IC 95%, 1, 13–7, 30)) y cuando el riesgo de aneuploidía es alto, paradójicamente el riesgo de aborto después de una BVC se reduce (RM, 0, 47 (IC 95%, 0, 28–0, 76)), presumiblemente debido al diagnóstico prenatal y a la interrupción de embarazos con aneuploidías importantes que, de otro modo, hubieran provocado un aborto espontáneo. Por ejemplo, en una paciente para quien el riesgo de aneuploidía es de 1 entre 1000 (0, 1%), el riesgo de aborto después de la BVC aumenta al 0, 3% (0, 2 puntos porcentuales más alto). Conclusiones: El riesgo de aborto espontáneo en las mujeres que se someten a una BVC es aproximadamente un 1% mayor que el de las mujeres a las que no se les hace, aunque este exceso de riesgo no se atribuye únicamente al procedimiento agresivo sino, en cierta medida, a las características demográficas y del embarazo de cada paciente. Después de tener en cuenta estos factores de riesgo y limitar el análisis a los embarazos de bajo riesgo, la BVC parece triplicar aproximadamente el riesgo de aborto en comparación con el riesgo de fondo de la paciente. Aunque se trata de un aumento sustancial en términos relativos, en los embarazos sin factores de riesgo de aborto, después de una BVC el riesgo de aborto sigue siendo bajo y similar, o ligeramente superior, al de la población en general. Copyright © 2020 ISUOG. Published by John Wiley & Sons Ltd. 摘要: 评估绒膜绒毛取样后流产风险的新方法 目的: 评估与绒膜绒毛取样(CVS)相关的流产风险。 方法: 这是一项回顾性队列研究，参与对象是2007年7月至2018年6月之间在西班牙、比利时和保加利亚的八所胎儿医学中心之一参加常规超声检查的孕妇(孕期在11周至13周零6天之间)。研究包含两类群体:(1)在西班牙穆尔西亚自治区阿瑞夏卡贞女大学临床医院进行评估的处于早期妊娠的所有单胎孕妇，她们没有经历过CVS(即非CVS组)；以及(2)在八所参与研究的中心之一进行早期妊娠评估后经历过CVS的 所有单胎孕妇(即CVS组)。我们排除了在出生前后被诊断为遗传异常或重大胎儿缺陷的妊娠，即那些导致妊娠终止或在孕期晚期经历过羊膜穿刺术的孕妇。我们采用了倾向度(PS)匹配分析来评估CVS与流产之间的关联。在PS匹配(1:1的比率)后，我们对比了CVS组和非CVS组的流产风险。该过程创造出两个可比较组，平衡了与CVS相关的产妇及孕期特征，类似于随机临床试验中进行的随机化。 结果: 研究人群由非CVS组中的22250个妊娠和CVS组中的3613个妊娠组成。CVS组中的流产发生率(2.1%; 77/3613)比非CVS组中的流产发生率(0.9% (207/22 250); P<0.0001)要高得多。PS算法将2122个CVS与2122个非CVS相匹配，CVS组和非CVS组分别有40(1.9%)和 55(2.6%)个妊娠发生了 流产(比值比(OR)，0.72(95% CI, 0.48–1.10)；P=0.146)。我们发现，继CVS后的流产风险与异倍体风险之间有较大的相互影响，暗示了根据背景特征CVS对流产风险的影响有所不同。具体来说，当异倍体风险低时，CVS后的流产风险增加(比值比，2.87(95% CI, 1.13–7.30))，而当异倍体风险高时，CVS后的流产风险却反常地降低了(比值比，0.47(95% CI, 0.28–0.76))，这可能归因于对重大异倍体(此情况原本就会导致自发性流产) 的产前诊断和终止妊娠。例如，一个患者的异倍体风险为千分之一(0.1%)，CVS后的流产风险将增至0.3%(增加了0.2个百分点)。 结论: 经历过CVS的孕妇的流产风险比没有CVS的孕妇约高1%，尽管该增余风险并不单独归因于入侵性检查，但是在一定程度上，归因于患者的特定年龄段和妊娠特征。在解释了这些风险因素并将分析限制在低风险妊娠之后，CVS似乎将流产风险增加到患者背景风险的约三倍以上。尽管这相对来说是一个重大的增加，在无流产风险因素的妊娠中，CVS后的流产风险仍然是低的，类似于或略高于一般人群的情况。版权 © 2020 ISUOG。由威利父子公司(John Wiley & Sons Ltd)出版。